Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ina.12085
|View full text |Cite
|
Sign up to set email alerts
|

Home interventions are effective at decreasing indoor nitrogen dioxide concentrations

Abstract: Nitrogen dioxide (NO2), a by-product of combustion produced by indoor gas appliances such as cooking stoves, is associated with respiratory symptoms in those with obstructive airways disease. We conducted a three-armed randomized trial to evaluate the efficacy of interventions aimed at reducing indoor NO2 concentrations in homes with unvented gas stoves: (i) replacement of existing gas stove with electric stove; (ii) installation of ventilation hood over existing gas stove; and (iii) placement of air purifiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…In a prior study, we found that week-long NO 2 concentrations in home with gas cooking appliances decreased following replacement of the gas stove with an electric stove and with installation of a HEPA and carbon filter. [33] However, replacement of a stove may not be a feasible solution for all homes, and previous research suggests that compliance with continuous use of an air purifier is relatively low, with air purifiers being used on only about 60% of days in a randomized trial of air cleaners. [34] Thus, targeted use of air purifiers or ventilation hoods during periods of use of combustion sources that contribute to short-term increases in NO 2 concentrations may be associated with higher compliance, be more cost-effective, and therefore more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, we found that week-long NO 2 concentrations in home with gas cooking appliances decreased following replacement of the gas stove with an electric stove and with installation of a HEPA and carbon filter. [33] However, replacement of a stove may not be a feasible solution for all homes, and previous research suggests that compliance with continuous use of an air purifier is relatively low, with air purifiers being used on only about 60% of days in a randomized trial of air cleaners. [34] Thus, targeted use of air purifiers or ventilation hoods during periods of use of combustion sources that contribute to short-term increases in NO 2 concentrations may be associated with higher compliance, be more cost-effective, and therefore more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, defining the harmful impact of indoor air quality on COPD morbidity is of utmost importance as indoor air pollution is a highly modifiable exposure. Feasible interventions that improve in-home air quality (111113) and optimize indoor temperature (114) may represent cost-effective and novel therapeutic arenas for a disease with limited treatment options.…”
Section: Indoor Air Pollution and Copdmentioning
confidence: 99%
“…One randomized controlled trial found reductions of 40% to 50% in indoor NO 2 concentrations when a gas stove was replaced with an electric one. 74 Whether this degree of indoor NO 2 reduction results in improvements in asthma remains unclear, however.…”
Section: Nomentioning
confidence: 99%